Oblique lateral interbody fusion in heterogenous lumbar diseases: Anterolateral screw fixation vs. posterior percutaneous pedicle screw fixation – A single center experience - Wu, Meng-Ting; Chung, Tzu-Tsao; Chen, Shao-Ching; Kao, Tzu-Jen; Song, Wen-Shin (Frontiers in Surgery, 2022)
Background Oblique lateral interbody fusion (OLIF) is a type of minimally invasive lateral lumbar interbody fusion technique used for treating lumbar degenerative diseases. This study aimed to analyze the clinical and radiographic efficacy of OLIF with anterolateral screw fixation alone and OLIF requiring fixation with conventional posterior percutaneous pedicle screws for lumbar diseases. Methods Medical records of consecutive patients admitted to Cheng-Hsin Hospital who received OLIF between January 2019 and December 2020 were retrospectively reviewed. Patients were divided into two groups by screw fixation: patients who received anterolateral screw fixation alone were defined as one-stage OLIF (n=9) and patients who received fixation with conventional posterior percutaneous pedicle screw were defined as two-stage OLIF (n=16). Patient clinical characteristics, medical history, intraoperative blood loss, length of hospital stay, peri-operative, and post-operative complications were evaluated in all patients. Results During the study period, a total of 25 patients were successfully treated with OLIF (n=9 one-stage; n=16 two-stage). Two-stage OLIF was associated with longer operation times, longer hospital stays, shorter bed-rest time, and a greater likelihood of having a blood transfusion compared with the one-stage OLIF group. A higher proportion of grade I subsidence was observed at 6 months and 1 year after surgery in the two-stage group compared with the one-stage group. Post-operative complications included ileus, dystonia, and dystonia were higher in the two-stage OLIF group. Improvements in radiographic parameters were demonstrated after OLIF, and the improvements were comparable between one-stage and two-stage OLIF. Conclusions One-stage OLIF is a feasible and efficacious treatment method for single- and multiple-level degenerative lumbar diseases. Additional clinical follow-up is necessary to confirm long-term outcomes.